2015
DOI: 10.1080/02640414.2015.1022575
|View full text |Cite
|
Sign up to set email alerts
|

Typical weekly workload of under 15, under 17, and under 19 elite Portuguese football players

Abstract: This study aims to describe the time-motion and physiological performance profiles of footballers whose ages are under 15 (U15), under 17 (U17), and under 19 (U19) during a typical week of a competitive season. A total of 151 elite Portuguese players U15 (age 14.0 ± 0.2; n = 56), U17 (age 15.8 ± 0.4; n = 66), and U19 (age 17.8 ± 0.6; n = 19) were monitored during 33 training sessions (TSs) (U15 n = 12; U17 n = 11; and U19 n = 10 TSs). The TS data were captured at 15 Hz by global positioning systems devices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 33 publications
10
85
1
1
Order By: Relevance
“…26%. These results are in line with findings in elite youth players that revealed that the workload was increasing until the last middle-week session [22]. At that moment, it was observed that the most demanding tasks were associated with tactical development and match.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…26%. These results are in line with findings in elite youth players that revealed that the workload was increasing until the last middle-week session [22]. At that moment, it was observed that the most demanding tasks were associated with tactical development and match.…”
Section: Discussionsupporting
confidence: 91%
“…This may suggest the caution of coaches to provide an optimal recovery period, thus opting for an increase in the training load in middle-week sessions. A similar study conducted in elite youth players verified that the post-match period was bound with lower values of distance covered, body impact, and time spent in highest HR zones [22]. The results of the present study also revealed that the most intense training sessions occurred in middleweek, more particularly 4 days after match.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In a secondary application, the use of performance groups would facilitate talent identification from a physical point of view (sprinting). Four performance groups have been used previously in a study on youth categories in soccer (Coutinho et al, 2015). A one-way analysis of variance (ANOVA) compared A, B, C and D groups for anthropometric characteristics and short-term power.…”
Section: Resultsmentioning
confidence: 99%